Analisis Faktor-Faktor Yang Mempengaruhi Kepatuhan Wajib Pajak UMKM Selama Pandemi Covid-19 - Nathania Aldisa Oliviandy; Titiek Puji Astuti; Faiz Rahman Siddiq (Universitas Negeri Padang, 2021)
This study aims to obtain empirical evidence the affect of tax rates, knowledge and understanding of taxation, perceptions of the effectiveness of the taxation system, and the level of trust in the legal and government systems towards taxpayer compliance. The sample in this study was taken using a purposive sampling method. The number of sample data processed was 340. Data collection using primary data sources in the form of a questionnaire was arranged with a five-point Likerts scale. The data analysis technique of this study used multiple linear regression analysis techniques. The result of analysis data in this research shows that the tax rate, knowledge and understanding of taxation, and the level of trust in the legal and government systems has a positive effect on taxpayer compliance, while the perceptions of the effectiveness of the taxation system has a negative effect on taxpayer compliance.Keywords: Knowledge; Effectiveness; Legal; Taxpayer Compliance.